PENGARUH CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP LUAS PENGUNGKAPAN INFORMASI STRATEGIS - Sinung Primastuti; Achmad Tarmizi (Diponegoro Journal of Accounting, 2012)
This study aimed to examine the effect of corporate governance and firm characteristics on the level of strategic information disclosure. Elements of corporate governance that are used to test the level of strategic information disclosure consist of managerial ownership, institutional ownership, the number of commissioners, the proportion of independent commissioners, and the number of board meetings. Then, for the characteristics of firms using firm size, leverage, and profitability. Retrieval of data in this study using purposive sampling method in manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the year 2009-2010. The samples of this study as many as 128 companies, and for the items strategic information disclosure take from research of Sanchez, Dominguez, and Alvarez (2010) which is about 8 items. The data of this study were tested using multiple regression analysis. The results show that managerial ownership, the proportion of independent commissioners, company size and profitability are significant and positive effect to strategic information disclosure. While institutional ownership and leverage significant and negative effect, then the number of commissioners and the number of board meetings did not effect to strategic information disclosure.